Measurement of the cross section for prompt isolated diphoton production in p(p)over-bar collisions at root s=1.96 TeV - Aaltonen, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
This article reports a measurement of the production cross section of prompt isolated photon pairs in proton-antiproton collisions at √s=1.96TeV using the CDF II detector at the Fermilab Tevatron collider. The data correspond to an integrated luminosity of 5.36fb-1. The cross section is presented as a function of kinematic variables sensitive to the reaction mechanisms. The results are compared with three perturbative QCD calculations: (1) a leading-order parton shower Monte Carlo, (2) a fixed next-to-leading-order calculation and (3) a next-to-leading-order/next-to-next-to-leading-log resummed calculation. The comparisons show that, within their known limitations, all calculations predict the main features of the data, but no calculation adequately describes all aspects of the data. © 2011 American Physical Society.